Integration of Existential Intelligence and Levels of Reason in Strengthening Spirituality Through Islamic Education - Abu Darda; Sayyida Nafisa Al-Razi; Muhammad Thoriqul Islam; Thias Arisiana; Syaiful Alim; Zainur Rofik (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Islamic education in various educational institutions is generally still oriented towards cognitive-textual aspects, emphasizing memorization, and is not yet effective in developing students’ overall spirituality. The existential intelligence proposed by Howard Gardner emphasizes a person’s ability to explore questions about the meaning of life, the purpose of existence, and the relationship between existence and transcendent reality. On the other hand, Ibn Sina explained the levels of reason, which consist of al-‘aql al-Hayulani, al-‘aql bi al-Malakah, al-‘aql bi al-Fi’il, and al-‘aql al-Mustafad as stages of development towards intellectual and spiritual enlightenment. This study uses library research. The data were collected through a review of primary sources, including Howard Gardner’s works Frames of Mind: The Theory of Multiple Intelligences and Intelligence Reframed: Multiple Intelligences for the 21st Century, and Ibn Sina’s an-Nafs. Secondary sources came from various journals, books, and scientific articles discussing existential intelligence and levels of reason. This study referred to Krippendorf’s content analysis principles. The integration of these two concepts results in a holistic, transformative, and reflective PAI learning model. This model combines Gardner’s existential questions with Ibn Sina’s process of strengthening reason, enabling students to develop a deep spirituality and interpret Islamic teachings in real life.